Fashion Brands Identity Through the Use of Slogans: A Stylistics Analysis - Nurhadi, Muizzu; Silalahi, Pininta Veronika; Arsa, Shabrina Dwi; Bramantyo, Agiel (CV. Era Digital Nusantara, 2023)
This research discusses how style has a role in enlivening each word and sentence in the slogan of a brand product in the sphere of advertising from time to time. Through the qualitative descriptive analysis, this research analyses ten slogans from several brand classes, especially on products that have class categorization with stylistic devices to find out the identity function embedded in each word or sentence. The research results show that stylistic devices, especially through lexical features such as vocabulary selection, parts of speech, and metaphor, as well as understanding the deep context of each slogan can show their brand images in advertising. In this way, these stylistic devices sharpen the meaning and reflection of the identity desired by fashion brands to consumers.